Use of sexuality-focused entertainment media in sex education - Neustifter, Ruth; Blumer, Markie L.C.; O'Reilly, Jessica; Ramirez, Francisco (Sex Education: Sexuality, Society and Learning)
The literature on the impact of entertainment media on sex education is typically pathology-focused, unclear regarding the effects of such usage, and void of dialogue between those who actually work in the areas of sexuality education and entertainment. To address this gap, this paper is the product of joint authorship between media figures from varied sexually-focused programming fields and academics who teach and conduct research in the areas of sexuality and relational health. The authors focus on the role that various forms of entertainment media play in educating members of the public and college classrooms in the areas of sex and sexuality. Additionally, examples of the inclusion of entertainment media in educational contexts are discussed.